CEMARAN MIKROBA DAN KADAR AIR PADA PENYEDAP RASA ALAMI BERBAHAN DASAR TEMPE DAN UDANG EBI - Devita Yudhayanti; Erna Agung Rahmawati; Nurul Nafsika (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
The use of MSG in society is usually in the form of cooking spices or broth powder. In the market there are many types and brands. But now many people are starting to reduce the use of MSG, this is because they are starting to realize the dangers and side effects of excessive use of food additives. So many people are starting to shift to using natural flavorings, either derived from pure kitchen spices or natural flavorings. This research is descriptive experimental. This research began with the manufacture of natural flavorings based on tempeh and dried shrimp. Formulations were made for 2 types with different composition ratios of tempeh and shrimp. Both formulations resulting from the manufacture of natural flavorings were then tested hedonic, to obtain market preference results. Furthermore, both formulations were tested for organoleptic, water content and microbial contamination numbers in the form of total plate counts and yeast mold numbers. The purpose of this study was to create the right formulation and test the quality of water content and microbial contamination of the formulations obtained. It is hoped that this research can produce an appropriate formulation with good quality so that it can be used by the community. The conclusion of this study is that the Natural Flavoring Formula is acceptable to the public and meets the water content requirements of 3.94% and 3.96%. Meanwhile, ALT microbial contamination was 17.5 colonies/gram and 30 colonies/gram, respectively. The yeast count was 330 colonies/gram and 4050 colonies/gram